The Topographical Prints of Louis Meunier: A Study of a Representation of Spain in the Seventeenth Century and its Extended Afterlife - Ní Lideadha, Sorcha Máire (Trinity College Dublin. School of Histories & Humanities. Discipline of History Of Art, 2024)
This thesis examines the representation of Spanish and Portuguese cities in an album of topographical views made by Louis Meunier, a printmaker operating in Paris in the second half of the seventeenth century. The set of fifty-five etchings are a testimony to an extensive journey made by the printmaker in the early 1660s from Lisbon to Granada and up through the centre of the peninsula to Madrid, and are reflective of the short-lived period of peace after the Treaty of the Pyrenees that enabled greater communication and travel between France and Spain. With views of individual monuments, lively city squares, and the inner courtyards of palaces, Meunier's prints offered the most comprehensive vision in printed form of the built fabric of Iberian cities in over one hundred years. The first edition of Meunier's prints, introduced to scholarship for the first time in this study, was printed ca. 1662 as a presentation piece for Queen Marie-Thérése, the Spanish Infanta who arrived at the French court after her marriage to Louis XIV in 1660. Despite their exclusive origins, Meunier's prints of Spain were later transposed to the open market where they were reprinted multiple times at the hands of various publishers. Through these successive versions and the circulation of later appropriations, Meunier's prints became a paradigm for subsequent generations to imitate and came to represent the definitive image of Spain far into the eighteenth century. This study presents a critical departure from traditional approaches to Meunier's prints that have prioritised their testimonial value as historic documents. Using Meunier's depiction of Western Islamic architecture in Andalucía as a case-study, this research interrogates the perceived authenticity of his depictions, and demonstrates that they represent an outsider's view of the cities he visited, with little reference to the symbolism of history and myth that contributed to an intangible sense of place for their inhabitants. Furthermore, the success of Meunier's images in establishing an enduring and authoritative image of Spain is analysed against the backdrop of the underdeveloped nature of the Spanish print industry in the seventeenth and eighteenth centuries, thus providing insight into the adaptability of early modern print in the contexts of evolving functions and technologies.
APPROVED
Keywords: Art History; Print History; Spain; France; 17th Century; Court Studies; Topographical Print